Are restrictions in sales hours of alcohol associated with fewer emergency room visits in Lithuania? An interrupted time‐series analysis. (13th December 2022) - Jiang, Huan; Tran, Alexander; Petkevičienė, Janina; Štelemėkas, Mindaugas; Lange, Shannon; Rehm, Jürgen
Abstract: Introduction: On 1 January 2018, an amendment to the alcohol control law was introduced in Lithuania which, among other changes, reduced trading hours for alcoholic beverages by 4 h for weekdays and Saturdays, and by 9 h for Sundays. The objective of the current study was to quantify the potential association of this law with the numbers and types of emergency room (ER) visits in Lithuania, in general and specifically for Sundays, for all ER visits, for injury‐related ER visits and specifically for alcohol poisoning as a 100% alcohol‐attributable cause. Methods: Sex‐stratified time‐series analysis‐based models for the period 2016–2019 were used to test for associations and for potential alternative explanations (e.g., the increase in minimum legal drinking age, which occurred at the same time). Results: Overall, while the reduction in sales hours for both sexes was associated with slight increases in all types and in injury‐related ER visits on a weekly basis, the association with ER visits for alcohol poisoning was in the opposite direction for men in all models. Specifically, among men, it was associated with an approximate decrease of 20% of alcohol poisoning‐related ER visits on Sundays and an approximate decrease of 12% of alcohol poisoning‐related ER visits for all seven weekdays. Discussion and Conclusions: As predicted, restrictions on availability were associated with marked reductions in ER visits for alcohol poisoning in men. However, contrary to expectations, there were no overall reductions in overall ER visits, nor reductions in injury‐related ER visits.